PERENCANAAN DAN EVALUASI KURIKULUM BERBASIS VISI MISI DALAM PEMBENTUKAN KOMPETENSI LULUSAN DI MADRASAH TSANAWIYAH AN NAJAH PEKANBARU - Ramadhani, Fitri; Daulay, Nurhamizah; Mulia, Fitri (STKIP Pesisir Selatan, 2026)
This study aims to describe and analyze curriculum planning and evaluation based on the vision and mission in shaping graduate competencies at MTs An Najah Pekanbaru. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, observations, and document analysis involving the head of the madrasah, the vice principal for curriculum affairs, and teachers involved in curriculum development. The findings show that curriculum planning at MTs An Najah Pekanbaru is aligned with the madrasah’s vision and mission, which emphasize a balance between mastery of science and technology and the development of noble character, religious values, and love for the Qur’an. The curriculum is operationalized through subject mapping, integration of religious values, development of life skills, and strengthening of foreign language and technological competencies. Curriculum planning is conducted contextually and participatively, involving madrasah leaders and teachers, which supports the holistic development of graduate competencies. Curriculum evaluation is carried out continuously, covering learning outcomes, instructional processes, and students’ religious character development. Evaluation results are used as a basis for reflection and decision-making in curriculum improvement. This study concludes that vision- and mission-based curriculum planning and evaluation play a strategic role in shaping comprehensive graduate competencies and enhancing the quality of madrasah education.